2022
DOI: 10.48550/arxiv.2205.02196
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the monoid of partial isometries of a cycle graph

Abstract: In this paper we consider the monoid DPC n of all partial isometries of a n-cycle graph C n . We show that DPC n is the submonoid of the monoid PORI n of all oriented partial permutations on a n-chain whose elements are precisely all restrictions of the dihedral group of order 2n. For this purpose, a useful characterization of an oriented transformation is established first. Our main aims are to determine the rank and to exhibit a presentation of DPC n . We also describe Green's relations of DPC n and calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…They showed that DP(C n ) is an inverse submonoid of the monoid of all oriented partial permutations on a chain with n elements and, moreover, that it coincides with the inverse submonoid of I n formed by all restrictions of a dihedral subgroup of order 2n of S n . This fact motivated the authors of [17] to call DP(C n ) by dihedral inverse monoid on Ω n . Also in [17], it was determined the cardinal and rank of DP(C n ) as well as descriptions of its Green's relations and, furthermore, presentations for DP(C n ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They showed that DP(C n ) is an inverse submonoid of the monoid of all oriented partial permutations on a chain with n elements and, moreover, that it coincides with the inverse submonoid of I n formed by all restrictions of a dihedral subgroup of order 2n of S n . This fact motivated the authors of [17] to call DP(C n ) by dihedral inverse monoid on Ω n . Also in [17], it was determined the cardinal and rank of DP(C n ) as well as descriptions of its Green's relations and, furthermore, presentations for DP(C n ).…”
Section: Introductionmentioning
confidence: 99%
“…This fact motivated the authors of [17] to call DP(C n ) by dihedral inverse monoid on Ω n . Also in [17], it was determined the cardinal and rank of DP(C n ) as well as descriptions of its Green's relations and, furthermore, presentations for DP(C n ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation